Central Aortic Blood Pressure From Ultrasound Wall-Tracking of the Carotid Artery in Children: Comparison With Invasive Measurements and Radial Tonometry. Issue 5 (May 2015) - Milne, Laura; Keehn, Louise; Guilcher, Antoine; Reidy, John F.; Karunanithy, Narayan; Rosenthal, Eric; Qureshi, Shakeel; Chowienczyk, Phil J.; Sinha, Manish D.
Abstract : Differences between central aortic root (c) and peripheral (p) systolic blood pressure (SBP) may be particularly marked in children, but noninvasive methods for assessing cSBP in children have not been validated. We compared estimates of cSBP obtained from radiofrequency ultrasound wall tracking of the carotid artery (ART.LAB system) with that measured directly by a catheter in the aortic root at the time of arterial cannulation. Carotid waveforms were calibrated from invasive measurements of mean and diastolic pressures. In 9 children aged 10.5±5.0 years (mean±SD), cSBP obtained from carotid wall tracking was highly correlated with invasive measures of cSBP ( r =0.99) with mean (±SD) difference 3.9±2.5 mm Hg. Second, we compared values of cSBP obtained from the carotid with those obtained using noninvasive applanation tonometry at the radial artery and a radial-to-aortic transfer function (SphygmoCor). Both carotid and radial tonometric measurements were calibrated from the same peripheral mean and diastolic measurements of blood pressure obtained by sphygmomanometry. In 84 children aged 13.2±3.2 years, there was excellent agreement between the 2 methods ( r =0.95; P <0.001) with mean difference 0.71±3.7 mm Hg (95% confidence interval =−1.53 to 1.01). This invasive validation study confirms that cSBP as estimated by carotid wall tracking provides an acceptable measurement of true cSBP when calibration is from true mean and diastolic pressures. Close agreement of cSBP obtained by carotid wall tracking and radial tonometry suggests that these provide similar results when calibrated from the same peripheral blood pressure measurements.